Dietary pesticide exposure and non-communicable diseases and mortality: a systematic review of prospective studies among adults - Julia Baudry; Pauline Rebouillat; Cécilia Samieri; Justine Berlivet; Emmanuelle Kesse-Guyot (BMC, 2023)
Abstract Background Research on the effect of pesticide exposure on health has been largely focused on occupational settings. Few reviews have synthesized the associations between dietary pesticide exposure and health outcomes in non-occupationally exposed adults. Objective We aim to summarize the evidence regarding dietary pesticide exposure and non-communicable diseases (NCD) in adults, using a systematic review of prospective studies. Methods Electronic and manual searches were performed until July 2023. The inclusion criteria were the following: 1) adults aged ≥ 18years, 2) (non)-randomized trials, prospective cohort studies, 3) dietary exposure to pesticides. A bias analysis was carried out using the Nutrition Evidence Systematic Review guidelines based on the Cochrane ROBINS-I. Results A total of 52 studies were retrieved and 6 studies that met the above criteria were included. Studies were conducted either in France or in the United States. The studies investigated the risk of cancer (n = 3), diabetes (n = 1), cardiovascular diseases (n = 1), and mortality (n = 1). The quality of the studies varied with overall grades derived from the bias analysis ranging from low to moderate bias. The level of evidence was estimated as low for the risk of cancer while the grading was not assignable for other outcomes, as only one study per outcome was available. Conclusions Although further research is warranted to examine more in depth the relationships between low-dose chronic exposure to pesticides through diet and NCD outcomes in non-occupationally-exposed adults, studies suggest a possible role of exposure to dietary pesticide on health. Standardized methodological guidelines should also be proposed to allow for comparison across studies.